Inclusion effect of ginger and turmeric mixture combined with Lactobacillus spp. isolated from rumen fluid of cattle on health status and growth of broiler - Risdianto, D.; Suthama, N.; Suprijatna, E.; Sunarso, S. (Diponegoro University, 2019)
This study was conducted to evaluate the combination of ginger and turmeric extracts added with Lactobacillus spp. (GTL) on body resistance and productivity of broilers. 576 broilers with an initial body weight of 36 ± 0.99 g were used and were observed for 35 days. GTL containing ginger extract (0.2 g/liter), turmeric extract (0.4 g/liter) and Lactobacillus spp. (2,997 x 107 cfu/ml), and was given since 1-day old. Parameters observed were bursa fabriscius, spleen, and thymus weights, gluthationine peroxidase (GSH-Px), superoxide dismutase (SOD), Lactobacillus spp., Coliform, and Eschericia coli, feed consumption, body weight gain, and feed conversion ratio (FCR). A completely randomized design (CRD) was assigned with 3x4 factorial pattern (3 types of feed, 4 levels of GTL), with 4 replications (12 birds each). First factor, types of feed (A): self-formulated feed (A1), combination of self-formulated and commercial feed with 50 portion each (A2) and commercial feed (A3). Second factor, levels of GTL (B): 0 ml (B0), 2 ml (B2), 4 ml (B4) and 6 ml (B6) per litre drinking water. Data were subjected to ANOVA and continued to Duncan test at 5% probability. Results indicated that self-formulated feed with inclusion of GTL at 4 ml (A1B4) improve body resistance and increase production performance of broilers.